Adherence to Antipsychotics among Patients with Schizophrenia at Selected Tertiary Level Hospitals - Yakha, Bhim Maya; Das, Dorwin; Tiwari, Suraj; Sharma, Pujan (Journal of Advanced Academic Research, 2024)
Background: Schizophrenia is a severe mental disorder where nonadherence is present in patients so that relapse, rehospitalization and treatment resistant can occur.Objectives: To identify the level of adherence to antipsychotics among patients with schizophrenia and to find its association with socio-demographic variables.Materials and method: A descriptive, cross-sectional study design was used for the study. 422 samples were collected using the purposive sampling technique Data was collected by the face-to-face interview technique during March, April, and May 2023.  Questionnaire related to Socio-demographic information, standard valid tool Drug Attitude Inventory (DAI-10) was used as instrument. Data were analyzed using descriptive and inferential statistics with SPSS version 20.Results: The mean age of the respondents was 41.02, ±12.77. More than half52 (12.3%) of respondents were taking antipsychotics for more than 15 years. Majority of respondents 342 (81.0%) were taking atypical types of antipsychotics. Only 220 (52.1%) of respondents has moderate level of adherence towards antipsychotic medicine. Significant association was found between duration of illness and adherence level where p=0.006. There is mean difference found p=